Delivering a collaborative, discipline-specific, and equity, diversity, and inclusion-centered teaching assistant training program in the life sciences - Kabir Bhalla; Brenna N. Hay; Zachary Morse; Eden Fussner-Dupas; Marcia L. Graves (Journal of Microbiology & Biology Education)
ABSTRACT A growing number of Canadian universities are implementing teaching assistant (TA) training programs designed to support graduate student teaching. At the University of British Columbia (UBC), the Life Sciences Institute (LSI) hosts one of several provost-funded, discipline-specific TA training programs on campus. At its core, the LSI TA Training Program is a partnership between senior TAs and faculty from multiple departments. Together, we design and deliver a TA training curriculum tailored for teaching in the life sciences that centers equity and inclusivity, while building a supportive community of emerging educators. In this paper, we provide a brief historical overview of the LSI TA Training Program and describe our embedded values and initiatives, including a flagship TA training “boot camp,” workshops, social celebration events, and a year-round mentorship initiative. We also present evidence showing that participation in our TA training program increases confidence in evidence-based teaching strategies, including creating inclusive, equitable classroom environments. We also discuss lessons learned in developing and sustaining such a cross-departmental TA training initiative, highlighting the benefits of faculty-student collaboration and our approaches to ensure our program is sustainable while adapting to evolving TA needs. Our experiences highlight that grounding discipline-specific TA training in inclusive teaching prepares new TAs with relevant, practical skills and supports their confidence to be inclusive educators in the life sciences.